2021
DOI: 10.53889/ijses.v1i1.2
|View full text |Cite
|
Sign up to set email alerts
|

STEM Education Implementation in Indonesia: A Scoping Review

Abstract: In Indonesia, STEM education has been implemented in the learning process since 2014. The number of researches on the implementation of STEM education are increasing from year to year. Therefore, this research was conducted to map the all articles published online with the theme of STEM education implementation in Indonesia. The scoping review was carried out following the framework from Arksey & O'Malley (2005), with the following steps: (1) formulating research questions, (2) exploring research results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 17 publications
(18 reference statements)
3
19
0
3
Order By: Relevance
“…As shown in research articles that examined the development of STEM-based student worksheets, the use of STEM-based student worksheets was found to be able to increase students' learning motivation (Burke et al, 2020). In another educational journal article by Farwati et al (2021), it was revealed that in STEM-based learning, overall, students are highly motivated to learn science. According to the article, the researchers consider that the STEM approach can be a solution to increase student learning motivation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As shown in research articles that examined the development of STEM-based student worksheets, the use of STEM-based student worksheets was found to be able to increase students' learning motivation (Burke et al, 2020). In another educational journal article by Farwati et al (2021), it was revealed that in STEM-based learning, overall, students are highly motivated to learn science. According to the article, the researchers consider that the STEM approach can be a solution to increase student learning motivation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…STEAM merupakan pendekatan pembelajaran multidisiplin yang diintegrasikan untuk menumbuhkan dan meningkatkan keterampilan abad ke-21. Keterampilan yang dimaksud adalah keterampilan berpikir kritis, berpikir kreatif, komunikasi dan kolaborasi [5].…”
Section: Pendahuluanunclassified
“…Based on the research results of Aberilla et al (2021), it is necessary to develop a STEM-based learning design, which must be emphasized in the science curriculum. STEM education is implemented as a learning strategy and approach, integrated with other learning models, used as learning, and developed into teaching materials, modules, and learning media to improve skills in the 21st century (Farwati et al, 2021).…”
Section: Introductionmentioning
confidence: 99%